2011
DOI: 10.1037/a0023889
|View full text |Cite
|
Sign up to set email alerts
|

Starting off on the right foot: Common factor elements in early psychotherapy process.

Abstract: Effective psychotherapy builds on a strong foundation developing as early as the first session. The aim of this review is to identify clinical research related to nonspecific (i.e., common factors) treatment effects and to expand upon those findings in developing techniques for applied clinical practice. Clinicians across treatment modalities can implement these techniques that are informed by empirical evidence in an effort to develop a collaborative treatment relationship with new patients. Three therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 100 publications
2
39
0
4
Order By: Relevance
“…For example, the phase model of change has been empirically supported to indicate that common factors improve well-being, symptom reduction, and life functioning (Kopta et al 1994). Common factors have been shown to be especially essential within separate phases, such as positive expectancies, role preparation, and collaborative goal formation being particularly important within the early process of psychotherapy (see Defife and Hilsenroth 2011).…”
Section: Common Factorsmentioning
confidence: 97%
“…For example, the phase model of change has been empirically supported to indicate that common factors improve well-being, symptom reduction, and life functioning (Kopta et al 1994). Common factors have been shown to be especially essential within separate phases, such as positive expectancies, role preparation, and collaborative goal formation being particularly important within the early process of psychotherapy (see Defife and Hilsenroth 2011).…”
Section: Common Factorsmentioning
confidence: 97%
“…At a basic level, the importance of collaborative goal setting with any client in the rehabilitative process is a common factor underlying the effectiveness of a number of different treatment modalities (DeFife & Hilsenroth, 2011). In the present study, respondents noted that at times they deviated from priorities identified by their risk assessment tools in order to build a good working alliance, which meant putting some goals on the "back burner" until clients were motivated, as well as working collaboratively on goals clients found important.…”
Section: The Importance Of Specific Responsivitymentioning
confidence: 99%
“…Even before contact, patients have increased tension with both positive and negative expectations (DeFife and Hilsenroth, 2011). The patients wonder whether their symptoms are severe enough, and fear not being taken seriously.…”
Section: Discussionmentioning
confidence: 99%